Hegel as a Poet. Escaping from Escapes - Rocco Lozano, Valerio (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The present article analyses the main topics and some stylistic aspects of Hegel's poetic production, from 1796 to 1800. Not only Eleusis, his best known poem, but all Hegel's poetic compositions deal with the possibility of a reconciliation between nature and spirit, overcoming the dichotomies of Kantian philosophy. Hölderlin's influence and the possibility of an escape into the irrational are the main reasons that induce Hegel to write in verse. These two factors are also the main reasons for the subsequent abandonment of poetry by the author of the Phenomenology of the Spirit.
Keywords: Idealism; Romanticism; Hegel; Hölderlin; poetry; intuition; Eleusis; dog